2018
DOI: 10.1186/s12876-018-0846-3
|View full text |Cite
|
Sign up to set email alerts
|

Male sex and history of ischemic heart disease are major risk factors for anastomotic leakage after laparoscopic anterior resection in patients with rectal cancer

Abstract: BackgroundAnastomotic leakage (AL) is the most serious and common complication of surgery for rectal cancer, and associated risk factors remain unknown despite developments in laparoscopic surgery. The present study aimed to determine risk factors for AL after laparoscopic anterior resection (AR) of rectal cancer.MethodsThis retrospective cohort study extracted information from a prospective database of all consecutive colorectal resections that proceeded at Nippon Medical School Hospital between January 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
(28 reference statements)
7
12
0
1
Order By: Relevance
“…In addition, a poorer blood supply caused by a lower anastomotic level might be another reason for the high risks of AL. We also explored the relationship between AL and tumor location, but no statistically significant differences were observed, which was in line with some previous reports [35]. Given the difference about the length of the distal margin from the low border of the rectal tumor between tumors located above and tumors located below the peritoneal reflection, we believe the level of anastomosis may be a better index to predict AL than tumor location.…”
Section: Gastroenterology Research and Practicesupporting
confidence: 81%
“…In addition, a poorer blood supply caused by a lower anastomotic level might be another reason for the high risks of AL. We also explored the relationship between AL and tumor location, but no statistically significant differences were observed, which was in line with some previous reports [35]. Given the difference about the length of the distal margin from the low border of the rectal tumor between tumors located above and tumors located below the peritoneal reflection, we believe the level of anastomosis may be a better index to predict AL than tumor location.…”
Section: Gastroenterology Research and Practicesupporting
confidence: 81%
“…The prolongation of operation time is often associated with some unfavorable conditions, such as in obese male patients, in patients with tissue edema after radiotherapy, or in patients with previous cardiovascular diseases 4,17‐20 . Consistent with results of the above literature, our results show that patients undergoing transrectal NOSE have similar risk factors for AL.…”
Section: Discussionsupporting
confidence: 91%
“…According to those studies, the preoperative and intraoperative risk factors included the sex, operation time, and amount of intraoperative blood loss [13,14]. Several studies have concluded that male sex is a risk factor for AL [24,25]. Similarly, the findings of our analysis also indicated that males were at a significant risk of developing AL.…”
Section: Discussionsupporting
confidence: 57%